Securing coherence through sequence-signals - Ubalde, Dolores (Torres) 1922- (s.n.], 1965)
This study presented ways of teaching coherence through the use of sequence-signals. The first part which deals with a discussion of sequence-signals and their use is intended largely for the information of the teacher. The second part contains instructional materials consisting of suggestions for presenting various types of lessons on sequence and practice exercises illustrating the different kinds of sequence-signals.